2004
DOI: 10.1128/jb.186.19.6457-6464.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hetero- and Autoprocessing of the Extracellular Metalloprotease (Mpr) in Bacillus subtilis

Abstract: Most proteases are synthesized as inactive precursors which are processed by proteolytic cleavage into a mature active form, allowing regulation of their proteolytic activity. The activation of the glutamic-acid-specific extracellular metalloprotease (Mpr) of Bacillus subtilis has been examined. Analysis of Mpr processing in defined protease-deficient mutants by activity assay and Western blotting revealed that the extracellular protease Bpr is required for Mpr processing. pro-Mpr remained a precursor form in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Currently, a large proportion of the commercially available alkaline peptidases are produced by Bacillus species because of their high pH and temperature stability (Tari et al 2006). Bacteria of the genus Bacillus, usually secrete two types of extracellular peptidases, a neutral and an alkaline peptidase (Park et al 2004;Tang et al 2004). Significant keratinolytic and proteolytic activity was observed for all three species studied in this work and this activity responded to changes in pH and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a large proportion of the commercially available alkaline peptidases are produced by Bacillus species because of their high pH and temperature stability (Tari et al 2006). Bacteria of the genus Bacillus, usually secrete two types of extracellular peptidases, a neutral and an alkaline peptidase (Park et al 2004;Tang et al 2004). Significant keratinolytic and proteolytic activity was observed for all three species studied in this work and this activity responded to changes in pH and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports state that B. subtilis secretes several types of extracellular protease, including the alkaline serine protease subtilisin, neutral protease A, bacillopeptidase F, metalloprotease, neutral protease B, and cell wall-associated extracellular protease. 9,22,23) However, only one halotolerant protease from Bacillus subtilis has been reported.…”
Section: Fig 2 Effects Of Salt Concentration On the Activity And Stmentioning
confidence: 99%
“…In this work, we demonstrated that the genes coding for two B. subtilis minor extracellular proteases, Vpr and Mpr (36,39,40,65,66), are also repressed by CodY. CodY repression at the vpr locus is exerted by binding at the single CodY-binding site located in the vicinity of the transcription start point of the gene, implying that the mechanism of repression is by competition with RNA polymerase.…”
Section: Discussionmentioning
confidence: 93%